Sunteți pe pagina 1din 84

Seminar 1: LAGRANGE’S EQUATIONS

Problem 1. Atwood’s Machine

Atwood’s machine consists of two weights of mass m 1 and m 2 connecting by a string

of length l that passes over a pulley of a radius a and moment of inertia I (see Figure

in the Set of Problems). The string is assumed massless and inextensible, and the

pulley is frictionless. The number of degrees of freedom is obviously one, while the

total number of the coordinates describing the positions of the two masses are six.

However there exist ﬁve holonomic constraints: four of them prevents motion of the

masses in y and z directions, whereas the ﬁfth has the form

x 1 + x 2 + πa = l,

(1)

where x 1 and x 2 are the vertical positions of each mass relative to the center of the

pulley. So the number of the generalized coordinates must be 6 5 = 1. The natural

choice for this single generalized coordinate is x 1 x . The Lagrangian is expressed

through this coordinate as follows:

T

= 1 2 m 1 x˙ 2 + 2 m 2 x˙ 2 +

1

1 I x˙ 2

2

a

2

V = m 1 gx m 2 g (l πa x )

L = 2 m 1 + m 2 + 2 x˙ 2 + (m 1 m 2 )gx + m 2 g (l πa ).

1

I

a

Lagrange’s equations:

d ∂L = ∂L

∂x

dt ∂ x˙

m 1 + m 2 + 2 x¨ = ( m 1 m 2 )g.

I

a

(2)

(3)

The latter of these equations gives the ﬁnal acceleration of the system in the form

x¨ = (m 1 m 2 )g m 1 + m 2 +

I

a

2

.

(4)

As we see, if m 1 > m 2 , then m 1 falls with constant acceleration while m 2 rises with the

same acceleration. If m 1 < m 2 , the converse is true. At last, if m 1 = m 2 , each mass

remains at rest (or moves at constant velocity). Of course, you are well familiar with

these conclusions from elementary physics.

Problem 2. Double Atwood’s Machine

Let replace one of the weights in the simple Atwood machine by a second simple

Atwood machine. Then we obtain the system which is known as a compound , or a

double Atwood machine that is shown in Figure from the Set of Problems. For the

motion of this system there are two degrees of freedom: one is the freedom of mass 1

(and the attached movable pulley) to move up and down about the ﬁxed pulley, and the

second one is the freedom of mass 2 (and the attached mass 3) to move up and down

about the movable pulley. In general, to describe the conﬁguration of the system we

need to have 12 coordinates (3 for each mass m 1 , m 2 , m 3 plus 3 for a movable pulley).

Thus there must be 12-2=10 constraints. 8 of those constraints limits the motion of all

the components of the machine to only a single direction. To formulate the remaining

two constraints we assume for simplicity that the pulleys are massless, and their radii

are small compared with the lengths of the constraining strings l and l . Then the

constraints can be written in a simpliﬁed form as

(x p + x 1 ) l = 0 and (2x 1 + x 2 + x 3 ) (2l + l ) = 0,

(5)

where x i and x p are the vertical positions of the masses and movable pulley relative

to the center of the ﬁxed pulley (Note that the second constraint is coming from the

formula ( x 2 x p )+(x 3 x p ) = l and by using the ﬁrst constraint in the form x p = l x 1 ).

Let choose the generalized coordinates x and x , as shown in Figure. Then the

kinetic and potential energies as well as the resultant Lagrangian can be written down

as follows:

  2 m 1 x˙ 2 + 2 m 2 (x˙ + x˙ ) 2 + 1 2 m 3 (x˙ x˙ ) 2

T =

1

   = 1 2 m 1 x˙ 2 + 2 m 2 (x˙ + x˙ ) 2 + 2 m 3 (x˙

V =

L

1

m 1 gx m 2 g (l x + x ) m 3 g (l x + l x )

1

1

+ x˙ ) 2 + (m 1 m 2 m 3 )gx + (m 2 m 3 )gx + const

(6)

Lagrange’s equations

d

dt

d

dt

∂L = ∂L

∂ x˙

∂L = ∂L

∂ x˙

∂x

∂x ,

yield

m 1 x¨ + m 2 x x¨ ) + m 3 x + x¨ ) =

(m 1 m 2 m 3 )g

m 2 (x¨ + x¨ ) + m 3 x + x¨ ) = (m 2 m 3 )g

(7)

(8)

The accelerations can be found from an algebraic solution of this system of equations

as

(9)

x¨ = m 1 m 3 4m 2 m 3 + m 1 m 2 m 1 m 3 + 4m 2 m 3 + m 1 m 2

g

and

x¨ =

2m 1 (m 2 m 3 )

m 1 m 3 + 4m 2 m 3 +

m 1 m 2 g

We can see if m 1 = m and m 2 = m 3 = m than x¨ = 0 and x¨ = 0.

2

(10)

Problem 3. Particle Sliding on a Movable Inclined Plane

Consider a particle of mass m which is allowed to slide free along an inclined plane

of mass M . As shown in Figure from the Set of Problems, the inclined plane itself

is not ﬁxed but is also free to slide along a horizontal surface. Since both objects

are constrained to move along a single dimension, in this case there are two degrees

of freedom. So to describe the conﬁguration of the system we need two generalized

coordinates: one to specify the position of the inclined plane relative to some reference

point on the motionless horizontal surface and the other to specify the position of the

mass m on the inclined plane relative, say, to the top of the plane. We denote those

coordinates x and x , respectively. To calculate the total kinetic energy of the system

we introduce the velocity of the plane,

V = e x x,˙

(11)

and the velocity of the mass m in the laboratory reference,

v = V + v = e x x˙ + e θ x˙ ,

(12)

where e x and e θ are the unit vectors in the surface and in the plane, the latter being

directed down the plane at an angle θ relative to the horizontal surface.

The total kinetic energy is

where

T = T M + T m ,

(13)

T M = 1 2 M V · V = 2 M x˙ 2

1

T m = 1 2 m v · v = 2 m (e x x˙ + e θ x˙ ) · (e x x˙ + e θ x˙ ) = 1 2 m (x˙ 2 + x˙ 2 + 2x˙ x˙ cos θ ) (14)

1

The expression for the potential energy depend on the choice of zero point. If we choose

it to be the top of the plane, then we may write

V = mgx sin θ.

Therefore, the Lagrangian of the system is

L

1

1

= 2 M x˙ 2 + 2 m (x˙ 2 + x˙ 2 + 2x˙ x˙ cos θ ) + mgx sin

 (15) θ, (16)

and the equations of motion are

d

dt

d

dt

∂L = ∂L

∂ x˙

∂L = ∂L

∂ x˙

∂x

∂x

,

or

d

dt [ m (x˙ + x˙ cos θ ) + M x˙ ] = 0 dt (x˙ + x˙ cos θ ) = g sin θ.

d

(17)

(18)

We notice that the time derivative of the quantity

[m (x˙ + x˙ cos θ ) + M x˙ ]

(19)

iz zero. This quantity is therefore a constant of motion. Close examination of this

quantity reveals that it is the total linear momentum of the system in the x direction.

From the Newtonian viewpoint, it means that there is no net force on the system in

the x direction - and this result seemingly falls out of the Lagrangian formalism! Note

also that this result follows from the fact that the Lagrangian is independent of the

coordinate x , i.e., L = 0.

∂x

Carring out the time derivatives in (18), we obtain the equations

m x + x¨ cos θ ) + M x¨ = 0

x¨ + x¨ cos θ = g sin θ.

(20)

Finally, solving these equations for x¨ and x¨ , we ﬁnd the accelerations

x¨ =

g sin θ cos θ

(m + M )/m cos 2 θ

(21)

and

(22)

1 m cos 2 θ/(m + M ) This particular example illustrates clearly the ease with which quite complicated

problems of mechanics fall apart when attacked within the Lagrangian approach. You

could certainly try to solve such the problems using the conventional Newtonian meth-

ods, but such an attempt would require a great deal more thought and physical insight

than demanded if Lagrange’s equations are used.

g sin θ

x¨ =

Problem 4. Simple Model of Coupled Harmonic Oscillators

Consider two identical particles of mass m attached to the three springs of stiﬀness

k , as shown in Figure from Set of Problems. We assume that the masses are restricted

to move in a straight line, so that the number of degrees of freedom is 2. The natural

choice for the generalized coordinates are the positions of the masses, which we denote

x 1 and x 2 . The kinetic and potential energies in terms of these variables are

This yields the Lagrangian

T =

V

1

2 m (x˙ 2 + x˙ 2 )

1

2

1

= 2 k (x 2 + x 2 + (x 2 x 1 ) 2 )

1

2

L

1

= T V = 2 m (x˙ 2

1 + x˙ 2

2 ) k (x 2 + x 2

1

2 x 1 x 2 )

and Lagrange’s equations

m x¨ 1 + k (2x 1 x 2 ) =

m x¨ 2 + k (2x 2 x 1

0

) = 0

(23)

(24)

(25)

By adding and subtracting these equations we derive the equations

m x 1 + x¨ 2 ) + k (x 1 + x 2 ) = 0

(26)

and

(27)

These are the harmonic equations with respect to x 1 ± x 2 , and hence their solutions

can be written as

(28)

and

(29)

where

(30)

a j and δ j (j = 1, 2) are the arbitrary constants.

Adding and subtracting once again, we ﬁnally obtain the general solution of the

equations of motion in the following form:

m x 1 x¨ 2 ) + 3k (x 1 x 2 ) = 0

(subtracting)

x 1 + x 2 = a 1 cos(ω 1 t δ 1 )

x 1 x 2 = a 2 cos(ω 2 t δ 2 ),

ω 1 = m ,

k

ω 2 = 3k

m

x

1

2 a 1 cos(ω 1 t δ 1 ) + a 2 cos(ω 2 t δ 2 )

1

  x 2 = 1 2 a 1 cos(ω 1 t δ 1 ) a 2 cos(ω 2 t δ 2 )

=

(31)

This solution reveals the existence of the two distinct modes. The mode with the eigen-

frequency ω 1 corresponds to the movement of the particles with the same amplitudes

and the same phases. In process of such oscillations the length of the spring between

the particles doesn’t change. The mode with the eigenfrequency ω 2 corresponds to the

movement of the particles with the same amplitudes but opposite phases. In this case

the center of mass is motionless. The general solution is the superposition of these two

modes. We will discuss this problem in the frame of theory of small oscillation during

the Seminar 6 (Problem 23 from the Set of Problems).

SEMINAR 2. PENDULUMS

Problem 7. Simple Pendulum

A simple pendulum means a mass m suspended by a string or weightless rigid rod of

length l so that it can swing in a plane. The y-axis is directed down, x-axis is directed

horizontally,i.e.

x = l sin θ, y = l cos θ . The kinetic energy is then

T

= 1 2 mv 2 = 2 m x 2 + y¨ 2 )

1

=

1

2 m (l θ ) 2 .

˙

(1)

If we put the potential energy to be zero when the string is horizontal, then at angle θ

it is

(2)

V = mgl cos θ.

So the Lagrangian is

1

L = T V = 2 ml 2 θ 2 + mgl cos θ,

˙

which yields Lagrange’s equation of motion

d

dt ml 2

˙

θ 2

+ mgl sin θ = 0,

(3)

(4)

or

¨

θ +

g sin θ = 0.

l

(5)

This equation looks simple but, in general, it is not easy to solve. However, if we

assume that the oscillations are small (say, θ << π/2), then sin θ can be approximated

by θ , and Eq. (5) takes the form of the usual linear equation for a simple harmonic

motion, namely

(6)

θ + g θ = 0,

¨

l

or

¨

θ + ω 2 θ = 0,

(7)

where

ω 2 =

g l .

The solution of this equation is well-known:

(8)

θ = C cos(ωt + δ ),

(9)

where ω and δ are the angular frequency and the phase of the oscillations, while C is

arbitrary constant which determine the amplitude of the oscillations. The period of

the oscillations is then

T = 2π = 2π g .

l

(10)

ω

Note that the period of oscillations is independent of the amplitude, provided the

amplitude is small enough so that Eq. (7) is a good approximation.

Now we return back to the consideration of the pendulum equation in its general

˙

form (5). Multiplying both sides of it by θ and integrating, we obtain

or

and

θ ˙ θ ¨ =

θd ˙ θ ˙ =

g sin

l

g

l

˙

θ θ,

sin θ dθ,

1

θ 2 = g cos θ + const.

˙

2 l

(11)

(12)

(13)

For a moment, let use this equation for ﬁnding the period in a particular case of large-

amplitude swinging when the pendulum is going back and force between the turning

points 90 and +90 . By deﬁnition, in these points

˙

θ = 0,

(14)

so the constant in (13) must be zero, and we have

1

2

˙

θ 2 = g cos θ,

l

= 2 g

dt

l

cos θ,

cos θ = 2 g

l

dt.

(15)

By observation that in our particular case the change in θ from θ = 0 to θ = 90

corresponds just one-quarter of a period, it follows

π/ 2

0

cos θ = 2g

l

T /4

0

dt = 2g · T

l

4

.

that is the period of the 180 swings is

T = 4

l

2g

π/ 2

0

cos θ .

(16)

(17)

You might be familiar with the function involved in the r.h.s. of this expression: it is

nothing but a particular case of the Beta or B-function .

Finally, let consider swings of any amplitude, say α . Then we may use the turning-

point-condition (14) with θ = α which leads to the relation

θ 2 = 2g (cos θ cos α ).

˙

l

(18)

Hence Eq. (17) must be changed to

T α = 4

 α l 2g 0 dθ √ cos θ − cos α .

(19)

Here T α is the period for swings from α to +α and back. The integral involved in

this expression can be transformed to a table integral as follows:

I =

cos θ = 1 2 sin 2 θ

cos α = 1 2 sin 2

2

α

2 cos θ − cos α = 2(sin 2 α − sin 2
2
2 θ )
α
α
α
1
=
√ cos θ − cos α
√ 2(sin 2 α − sin 2 θ
) =
2
0
0
0
sin 2 θ
2
2
2
1 −
sin α
sin 2 α
2
2

Introduce new variable:

In terms of this variable x = sin θ
sin α
cos θ
2
2
dx = 1
2 sin α
2
2

(20)

(21)

I = 2

1 dx

0

(1 x 2 )(1 x 2 sin 2 α )

2

2K sin α ,

2

(22)

where we used the notation K for an elliptic integral. Thus the period (19) takes the

form

(23)

T α = 4 l

2g 2K sin α = 4 g K sin α .

2

l

2

This expression for the period can be used to exactify the value of the period as com-

pared with its small-oscillation approximation given by Eq. (10) due to the existence

of the following expansion for an elliptic integral:

K sin α = π 1 + 1 2 2 sin 2 α + 1 · · 3 4 2 sin 4 α +

2

2

2

2

2

(24)

For α small enough so that sin α/2 can be approximated by α/2, it follows

K sin α = π 1 + α 16 +

2

2

2

,

and hence the period can be approximated as

T α = 2π g 1 + α 16 +

l

2

(25)

(26)

We see that this formula diﬀers from our previous one for simple harmonic motion,

T = 2π l/g , by the presence of the second- (and higher-)order terms on α . Naturally,

for very small α this diﬀerence is negligible. However, for somewhat large α , say, α =

T α = 2π g 1 + 64 +

l

1

(27)

It means, for example, that a pendulum started at 30 would get exactly out of phase

with a pendulum started at very small angle in about 32 periods.

Physically, the motion of a pendulum at diﬀerent amplitudes can be easily under-

stood if we consider the sum of the kinetic and potential energy,

1

T + V = 2 ml 2 θ 2 mgl cos θ = E,

˙

(28)

where E is the initial energy level of the system. The potential energy V (θ ) is

mgl cos θ . We see that for

mgl < E < mgl,

(29)

the motion is oscillating one because of the existence of the turning point where the

total energy is equal the potential energy. On the other hand, for

E > mgl,

(30)

there is no turning point, and the motion is nonoscillatory: θ is steadily increases or

˙

steadily decreases, while θ oscillates between a maximum and minimum value, as cabn

˙

be shown in the phase diagram θ = f (θ ) . In this case a pendulum has enough energy

to swing around in a complete circle. Note that this motion is not oscillatory but

still periodic, a pendulum making one complete revolution each time θ increases or

decreases by 2π . Finally, for

(31)

E = mgl,

there exist the positions

θ = ±(2n + 1) π, (n = 0, 1,

)

(32)

which are called the bifurcation points of the solution of the equation of motion for a

simple pendulum.

Problem 8. Double Pendulum

Consider the motion of a double pendulum that consist of two simple pendula, each

of mass m and lenght l , as shown in Figure from the Set of Problems. The ﬁrst one is

attached to a ﬁxed support, and the second one is attached to the mass of the ﬁrst. (a)

Assuming that the pendulum executes small oscillations conﬁned to a single plane, ﬁnd

the modes of oscillations. (b) Find numerically the general solution of the equations of

motion.

The conﬁguration of the system is speciﬁed by the two angles θ and ϕ , as shown

in the Figure. The Cartesian coordinates of the two masses relate to these generalized

coordinates according to:

x 1 = l sin θ

y 1 = l cos θ

x 2 = x 1 + l sin ϕ

y 2 = y 1 + l cos ϕ = l (cos θ + cos ϕ ).

= l (sin θ + sin ϕ )

The corresponding velocities are

˙

  x˙ 1 = l

θ θ

˙

  y˙ 2 = l (sin θ θ + sin ϕ ϕ˙ ),

cos θ θ

  y˙ 1 = l sin

˙

x˙ 2 = l (cos θ θ

˙

+ cos ϕ ϕ˙ )

(33)

(34)

so that the kinetic and potential energies are calculated as

and

T

1

2 + y˙ ) = 1 2 ml 2 [2 θ 2 + ϕ˙ 2 + 2 cos(θ ϕ ) θ ϕ˙ ]

2

2

˙

˙

= 2 m (x˙ 2 + y˙ + x˙ 2

1

2

1

V = mgy 1 mgy 2 = mgl (2 cos θ

+ cos ϕ ).

The Lagrangian

L = T V = 1 2 ml 2 [2 θ 2 + ϕ˙ 2 + 2 cos(θ ϕ ) θ ϕ˙ ] + mgl (2 cos θ + cos ϕ )

˙

˙

creates Lagrange’s equations of motion

¨

2 θ + ϕ¨ cos(θ ϕ ) + ϕ˙ 2 sin( θ ϕ ) + 2 g sin θ = 0;

l

¨ ˙

ϕ¨ + θ cos(θ ϕ ) θ 2 sin(θ ϕ ) + g sin ϕ = 0.

l

(35)

(36)

(37)

(38)

In general, this system of equations is rather complicated and it must be solved

numerically. The analytical solution can be obtained, as usual, in the case of small

oscillations when we can use the small angle approximation for all sine and cosine

functions involved, that is

cos(θ ϕ ) 1,

sin( θ ϕ ) (θ ϕ ),

sin θ θ

sin ϕ ϕ.

(39)

Substituting these expressions into the equations of motion and neglecting the higher-

order terms, we obtain the simpliﬁed version of these equations,

2 θ + ϕ¨ + 2ω θ = 0

(40)

¨

2

0

¨

ϕ¨ + θ + ω ϕ = 0,

0

2

where

ω 0 = g .

l

(41)

By substituting

θ = Ae

ϕ =

iωt

Be iωt ,

(42)

we transform Eqs. (40) to the set of the homogeneous algebraic equations for the

amplitudes A and B ,

(43)

2(ω 2 + ω )A ω 2 B = 0

2

0

ω 2 A + (ω 2 + ω

2

0

)B =

0

This set of equations has the nontrivial (i.e. nonzero) solution only if its determinant

is equal zero, det 2(ω 2 + ω

2

0

) ω 2 (ω 2 + ω

2

0

 ) = 0, (44) (45) (46) (47)

ω 2

or

which yields the equation

whose roots are 2
2(−ω 2 + ω ) 2 − ω 4 = 0,
0
2
4
ω 4 − 4ω ω 2 + 2ω = 0,
0
0
ω 1 , 2 = 2 ∓ √ 2 ω 0 .

These roots determines the two possible modes of small oscillations of a double pen-

dulum.

To understand the physical sense of these modes we substitute the frequencies ω 1

and ω 2 back into the set of equations (43). For ω = ω 1 , we obtain

(2 2 2)A + (2 2)B = 0

(48)

(2 2)A + (1 2)B = 0,

which yields

B = 2A.

(49)

For ω = ω 2 , we have

which yields

(2 + 2 2)A + (2 + 2)B = 0 (2 + 2)A + (1 + 2)B = 0,

B = 2A.

(50)

(51)

Hence the modes ω 1 and ω 2 can be naturally called the symmetric and antisymmet-

ric modes, respectively. It is interesting to notice that the ratio of these two mode

frequencies is independent of all the parameters m, l and g and is equal to

ω

2

ω

1

=

(2 + 2)

(2

2) 1 / 2

= 2. 414,

(52)

that is the oscillation in the faster, antisymmetric, mode has a frequency about two

and one-half times that of the slower, symmetric, mode.

Seminar 3: LAGRANGE’S EQUATIONS. II

Problem 10.

Two masses, 2m and m, are suspended from a ﬁxed frame by two elastic springs

of elastic constant k, as shown in Figure from the Set of Problems. Consider only

vertical motion.

 (a) Find the eigenfrequencies and normal modes of oscillations of this system. (b) The upper mass 2m is slowly displaced downwards from the equilibrium po-

sition by a distance l and then let go. Consider the subsequent motion of the lower

mass m.

Solution:

The system is speciﬁed by the two generalized coordinates y 1 and y 2 , and its kinetic

energy is

T =

1

2 2my˙

2

1

The potential energy is the sum

+

V

1

2 my˙

2

2 =

1

2 m(2y˙

2

1

= V 1 + V 2 ,

+ y˙

2

2

 ). (1) (2)

where V 1 and V 2 are the contributions from the two masses and two springs, respec-

tively. The ﬁrst contribution is

V 1 = 2mgy 1 mgy 2 = mg(2y 1 + y 2 ).

(3)

To calculate the second contribution we denote the natural length of the upper and

lower springs l 1 and l 2 . Then the changes of lengths of the springs due to the presence

of the two masses are as follows:[see Figure]

and

y 1 l 1

y 2 y 1 l 2 .

(4)

(5)

Thus the contribution into the total potential energy from the springs, V 2 , is

V 2 = 1

1

2 k(y 1 l 1 ) 2 + 2 k(y 2 y 1 l 2 ) 2 .

(6)

The resultant Lagrangian is

L = T V = T V 1 V 2 = 1 2 m(2y˙

2

1

+y˙

2

2

Lagrange’s equations

dt ∂y˙

d

∂L

i

1

)+2mgy 1 +mgy 2 2 k[(y 1 l 1 ) 2 +(y 2 y 1 l 2 ) 2 ].

(7)

∂L

i = 0

∂y

(i = 1, 2)

(8)

yield

2my¨ 1 + 2ky 1 ky 2

my¨ 2 + ky 2 ky 1 = mg + kl 2 .

= 2mg + kl 1 kl 2 ,

(9)

To simplify these equations we introduce new variables

η 1 = y 1 y 1 0

and η 2 = y 2 y 2 0 ,

(10)

where y 1,2 0 are the equilibrium positions of the masses 2m and m. These positions

may be found from the force equations

which give

3mg = k(y 1 0 l 1 )

mg = k(y 2 0 y 1 0 l 2 ),

ky 1 0 ky 2 0

=

=

3mg + kl 4mg + kl 1 + kl 2 .

1

(11)

(12)

In terms of new variables Eqs. (9) are rewritten as

2¨ 1 + 21 2 = 2mg + kl 1 kl 2 2ky 1 0 + ky 2 0 , mη¨ 2 + 2 1 = mg + kl 2 ky 2 0 + ky 1 0 .

(13)

Using the equilibrium values y 1,2 0 , given by Eq. (12), you can easily check that the

right-hand-sides of Eqs. (13) are identically zero, so these equations are in fact the

homogeneous equations, namely

2¨ 1 + 21 2 = 0, mη¨ 2 + 2 1 = 0.

With the trial solution of the type

η 1 = Ae iωt ,

η 2 = Be iωt ,

(14)

(15)

Eqs. (14) transform to the set of the linear algebraic equations which is written in

matrix form as

(16)

k k 2

This set has the nontrivial (i.e. nonzero) solution only if the secular equation

2k 2k

2

A

B = 0.

2k 22 k

k k 2

= 0

(17)

holds. This equation has two positive roots

ω 1,2 =

m 1 ± √ 2 ,

k

1

(18)

which deﬁne the eigenfrequencies of oscillations in the system. The corresponding

modes of oscillations follows from the relation

B 2k 22

A = 2.

=

k

We see that there are two modes,

2

1

and

2 .

1

(19)

(20)

These modes are usually called the normal modes of oscillations.

(b) To solve this problem we need to use the general solution of the problem which

we take in the form

η 1 =

η 2 = 2A 1 cos(ω 1 t + δ 1 ) + 2A 2 cos(ω 2 t + δ 2 ) .

A 1 cos(ω 1 t + δ 1 ) + A 2 cos(ω 2 t + δ

2

)

(21)

To determine the constants involved, we apply the initial conditions at t = 0:

η 1 (0) = η 2 (0) = l,

η˙ 1 (0) = η˙ 2 (0) = 0,

which yield

A 1 cos δ 1 + A 2 cos δ 2 = l

2A 1 cos δ 1 + 2A 2 cos δ 2 = l

ω 1 A 1 sin δ 1

ω 2 A 2 sin δ 2 = 0

2ω 1 A 1 sin δ 1 2ω 2 A 2 sin δ 2 = 0. The last two equations in this set gives

δ 1 = δ 2 = 0.

(22)

(23)

(24)

Then the rest of equations in (23) is simpliﬁed to the form

and we thus obtain

A 1 =

A 1 + A 2 = l 2A 1 + 2A 2 = l,

2 1

l

2

1

A 2 =

2 1 +

l

2 .

1

(25)

(26)

With these amplitudes and phases, we can easyly calculate the coordinate y 2 which

describe the motion of the mass 2m. Namely, we have

= l 1 + l 2 + 4mg +

k

1

2

y 2 = y 2 0 + η 2

2 l cos m 1 +

1

k

2 t +

1

1

2 +

2 l cos m 1

1

k

2 t

1

(27)

Problem 11.

The block B attached to a string of stiﬀness k with the mass m at the end oscillates

in the vertical direction,

s = A sin ωt.

(28)

Show that the motion of the mass m is described by the formula

where

Solution:

q(t) = C sin(ω 0 t + δ) +

2

0

2

ω 0

ω 2 sin ωt,

ω 0 = k

m .

From Figure in Set of Problems it follows

q(t) + l = l 1 (t) + s,

(29)

(30)

(31)

where l is the equilibrium value of the string length. Denoting l 0 the natural length

of the spring, we may express l as

l = l 0 + ∆l,

(32)

where ∆l is determined from an elementary balance of forces,

that is

k · l = mg,

l = mg .

k

(33)

(34)

Now we are able to calculate the kinetic, T , and the potential, V , energies as

and

T

= 1 2 mq˙ 2 ,

V = mgq+ 1 2 k(l 1 l 0 ) 2 = mgq+ 1 2 k(∆l+qs) 2 = mgq+

1 k mg

2

k

(35)

+qs 2 . (36)

Note that in these expressions the contributions from the block are absent because

the motion of the block is assumed to be known from the very beginning (it is given

by Eq. (28)).

Therefore, the Lagrangian of the system which we are interested in is

L

= 1

2 mq˙ 2 + mgq

1 k mg

2

k

+ q s 2 .

Lagrange’s equation

yield the equation of motion

dt ∂L

d

∂q˙

∂L ∂q

= 0

mq¨ mg + k mg

k

+ q s = 0,

or

q¨+ ω

2

0

q = ω

2

0

s,

(37)

(38)

(39)

(40)

where the use of the notation (30) has been made.

The solution of the eqution (40) consist of the sum of the general solution of the

homogeneous equation

q¨+ ω